AC impedance diagnosis of a 500W PEM fuel cell stack Part I: Stack impedance - Yuan, X.; Sun, J.C.; Blanco, M.; Wang, H.; Zhang, J.; Wilkinson, D.P.
Diagnosis of stack performance is of importance to proton exchange membrane (PEM)fuel cell research. This paper presents the diagnostic testing results of a 500W Ballard Mark V PEM fuel cell stack with an active area of 280 cm2 by electrochemical impedance spectroscopy (EIS). The EIS was measured using a combination of a FuelCon test station, a TDI loadbank, and a Solartron 1260 Impedance/Gain-Phase Analyzer operating in the galvanostatic mode. The method described in this work can obtain the impedance spectra of fuel cells with a larger geometric surface area and power, which are normally difficult to measure due to the limitations on commercial load banks operating at high currents. By using this method, the effects of temperature, flow rate, and humidity on the stack impedance spectra were examined. The results of the electrochemical impedance analysis show that with increasing temperature, the charge transfer resistance decreases due to the slow oxygen reduction reaction (ORR)process at low temperature. If the stack is operated at a fixed air flow rate, a low frequency arc appears and grows with increasing current due to the shortage of air. The anode humidification cut-off does not affect the spectra compared to the cut-off for cathode humidification.
Keywords: AC IMPEDANCE; ELECTROCHEMICAL IMPEDANCE SPECTROSCOPY (EIS); PROTON EXCHANGE MEMBRANE FUEL CELL (PEMFC); STACK